PERAN ORGANISASI MASYARAKAT SIPIL DALAM PENGELOLAAN KERAGAMAN DI SEKOLAH - Hendrik, Herman (Jurnal Penelitian Kebijakan Pendidikan, 2022)
This paper aimed to describe the roles of civil society organizations in managing diversity at schools. Civil society organization is an important element in a democracy. Their role in many aspects of life in Indonesia has been widely revealed, including in the education sector. Education in Indonesia reflects the character of Indonesian society in general, which is rich in diversity. Therefore, managing diversity in schools becomes a paramount issue. This is to anticipate the emergence of conflicts stemming from intolerance and inability to accept differences. This paper was written through library research. Data were collected from various sources: books, journals, reports, and websites containing information about civil society organizations and their work in managing diversity in education. Research findings revealed that a number of civil society organizations had played a role in managing diversity in education units through various activities such as trainings, seminars, and discussions. These various activities target almost every element in the school; namely students, teachers, and principals.